2008
DOI: 10.3200/jmbr.40.5.400-408
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Experience on Postural Control: Effect of Expertise in Gymnastics

Abstract: ABSTRACT. The authors investigated how expertise in motor skills that require fine postural control, such as gymnastics, influences postural regulation. Gymnasts and nongymnasts performed a postural stabilization task after anterior-posterior destabilization while looking at a target in front of them. The authors recorded and analyzed the center of pressure and the ankle, knee, and hip displacements. Gymnasts were able to react rapidly after destabilization to decrease their center of pressure and the angular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
41
1
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 33 publications
(61 reference statements)
4
41
1
4
Order By: Relevance
“…Enhanced stability might be a general feature of the advanced balance skill exhibited by dancers, as dancers have exhibited enhanced neuromuscular responses and proprioceptive sensitivity [1][2][3][4][5][6]. It is unclear whether greater postural coordination stability might be associated with speed of neuromuscular responses, but research does suggest these stability results could be related to enhanced proprioceptive sensitivity [16][17][18][19].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Enhanced stability might be a general feature of the advanced balance skill exhibited by dancers, as dancers have exhibited enhanced neuromuscular responses and proprioceptive sensitivity [1][2][3][4][5][6]. It is unclear whether greater postural coordination stability might be associated with speed of neuromuscular responses, but research does suggest these stability results could be related to enhanced proprioceptive sensitivity [16][17][18][19].…”
Section: Discussionmentioning
confidence: 99%
“…Studies that employed perturbations during static balance have reliably shown that experts exhibit faster postural responses resulting in greater overall stability [1,2,4]. These studies tell a more consistent story than those that employed quiet stance, yet an incomplete one.…”
mentioning
confidence: 91%
See 2 more Smart Citations
“…Corroborando esta idea varias investigaciones han demostrado que diferentes especialistas (bailarinas y practicantes de gimnasia artística) son significantemente más estables y menos dependientes de la visión que sujetos no entrenados [15][16][17] . Sin embargo, esta hipótesis no es plenamente aceptada, existiendo algunos trabajos donde no se demostró el efecto positivo que el entrenamiento pudiera tener sobre el control postural 18,19 . Además, la habilidad de gimnastas de élite para conseguir, de forma eficiente, posturas específicas de alta complejidad técnica no parece tener una transferencia positiva sobre la capacidad de mantener una adecuada postura erecta estática 20 .…”
Section: Introductionunclassified